2019
DOI: 10.1002/jnr.24544
|View full text |Cite
|
Sign up to set email alerts
|

Differential deletion of GDNF in the auditory system leads to altered sound responsiveness

Abstract: Glial‐derived neurotrophic factor (GDNF) has been proposed as a potent neurotrophic factor with the potential to cure neurodegenerative diseases. In the cochlea, GDNF has been detected in auditory neurons and sensory receptor cells and its expression is upregulated upon trauma. Moreover, the application of GDNF in different animal models of deafness has shown its capacity to prevent hearing loss and promoted its future use in therapeutic trials in humans. In the present study we have examined the endogenous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…FoxG1-deletion mice had significantly shorter cochlear ducts than normally developing mice and lacked the formation of the horizontal crista and ampulla (Pauley et al, 2006). In addition, the distribution of inner ear nerve fibers in FoxG1-deletion mice also showed abnormalities (Harasztosi et al, 2019). Hwang et al found that FoxG1 is essential for the formation and separation of the sensory cristae, indicating that FoxG1 has a function in regulating sensory fate in the inner ear (Hwang et al, 2009).…”
Section: The Role Of Foxg1 In the Inner Earmentioning
confidence: 99%
“…FoxG1-deletion mice had significantly shorter cochlear ducts than normally developing mice and lacked the formation of the horizontal crista and ampulla (Pauley et al, 2006). In addition, the distribution of inner ear nerve fibers in FoxG1-deletion mice also showed abnormalities (Harasztosi et al, 2019). Hwang et al found that FoxG1 is essential for the formation and separation of the sensory cristae, indicating that FoxG1 has a function in regulating sensory fate in the inner ear (Hwang et al, 2009).…”
Section: The Role Of Foxg1 In the Inner Earmentioning
confidence: 99%